2017
DOI: 10.18632/oncotarget.15420
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin inhibits the immediate-early response gene EGR1 and improves the functional profile of CD4+T-lymphocytes in acute coronary syndromes

Abstract: Background- Adaptive immune-response is associated with a worse outcome in acute coronary syndromes. Statins have anti-inflammatory activity beyond lowering lipid levels. We investigated the effects of ex-vivo and in-vivo atorvastatin treatment in acute coronary syndromes on CD4+T-cells, and the underlying molecular mechanisms.Approach and results- Blood samples were collected from 50 statin-naïve acute coronary syndrome patients. We assessed CD4+T-cell activation by flow-cytometry, the expression of 84 T-help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…The qualitative and quantitative assessment of the individual samples was determined using a dedicated software. The total RNA was reverse transcribed into cDNA by using iScript RT (Bio-Rad Laboratories, Hercules, CA) 82 . SYBR Green gene expression assays were performed according to the manufacturer’s instruction using the iQ™ SYBR® Green Supermix (Bio-Rad Laboratories, Hercules, CA) and the CFX96 Touch Real-Time PCR Detection System (Bio-Rad Laboratories, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative and quantitative assessment of the individual samples was determined using a dedicated software. The total RNA was reverse transcribed into cDNA by using iScript RT (Bio-Rad Laboratories, Hercules, CA) 82 . SYBR Green gene expression assays were performed according to the manufacturer’s instruction using the iQ™ SYBR® Green Supermix (Bio-Rad Laboratories, Hercules, CA) and the CFX96 Touch Real-Time PCR Detection System (Bio-Rad Laboratories, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that there is an association between heart disease and immune cells, including T cells as well as mononuclear macrophages, and ACS; [5][6][7] however, few studies have focused on further investigating this relationship and any possible mechanisms. This study aims to demonstrate changes of immune cells in three subtypes of ACS and explore potential mechanisms.…”
mentioning
confidence: 99%